Weak guidance modal cutoff analysis of a waveguide having a core cross section bounded by nonconcentric circles - Singh U.K.; Khastgir P.; Singh O.N. (My University, 2025)
We make an analytical study of the modal cutoff behavior of a waveguide with an annular core cross section bounded by two nonconcentric circles. The characteristic and cutoff equations are obtained with the use of the weak guidance approximation. Numerical computations show that the number of modes sustained is lowered as the concentric annular cross section becomes nonconcentric. © 1997 John Wiley & Sons, Inc.